On prime and congruence-prime acts over monoid with zero (in Ukrainian) - Yu. T. Bilyak; H. V. Zelisko; M. Ya. Komarnitskiy (Математичні Студії, 2013)
The properties of the prime and the congruence-prime acts over monoid with zero are investigated.